Genetic variation in the E6 and E7 genes of human papillomavirus type 16 in northeastern Argentina - Totaro, María Elina (2021)
The province of Misiones is considered a region with a high mortality rate due to cervical cancer (CC). To gain insight into this problem, we explored the association between genetic variation in the E6 and E7 oncogenes of HPV16 and the risk of CC. We studied 160 women with cytological diagnoses of negative for intraepithelial lesion or malignity, low-grade squamous intraepithelial lesion, and high-grade squamous intraepithelial lesion/CC and a positive test for HPV16 infection. The genetic characterization of E6 and E7 genes was undertaken through PCR amplification and direct Sanger sequencing. Phylogenetic classification was conducted using Bayesian methods. To estimate the odds ratio (OR) for an association between genetic variants in the E6 and E7 genes and the risk of CC, we used ordinal logistic regression adjusted by age. The final data set comprised 112 samples. Diagnostic single-nucleotide polymorphisms (SNPs) and phylogenetic trees confirmed the presence of Lineage A (95.5%) and D (4.5%) in the samples. For the E6 gene, we identified eleven different sequences, with the most common ones being Lineage A E6 350G (58.9%) and E6 350T (37.5%). The E6 350G was associated with progression to HSIL/CC, with an OR of 19.41 (4.95–76.10). The E7 gene was more conserved than E6, probably due to the functional constraints of this small protein. Our results confirmed the association of the E6 350G SNP with a higher risk of developing CC. These data will contribute to understanding the biological bases of CC incidence in this region.